Weavers of water canvases. The encounter between talent, place, and context - Minello, Rita (Formazione & insegnamento, 2019)
The fragility of science has led to the surpassing of technology, within a framework of rapid escalation. Such evidence brings about questions about life’s diachronic primacy and its refusal to make itself available in the age of reproducibility and manipulability. The safeguard of anthropological centrality amounts to understanding that new processes, which satisfy the needs of diverse educational regions, require the overcoming of challenges related to generativity and talent education. All of the above shall fit a significative framework, which results from contextual interactions.